Chambers essential English dictionary (Edinburgh, 1995)
The book contains 50.000 examples of real, everyday English, full-sentence definitions, thousands of synonyms and antonyms, plural of nouns, comparative and superlative forms of adjectives, and verb parts, 15 pages of illustrations for vocabulary-building
Keywords: english language - dictionaries